Multicomponent Approach to Bioactive Peptide–Ecdysteroid Conjugates: Creating Diversity at C6 by Means of the Ugi Reaction - Lesma, Giordano; Luraghi, Andrea; Rainoldi, Giulia; Mattiuzzo, Elena; Bortolozzi, Roberta; Viola, Giampietro; Silvani, Alessandra (Synthesis, 2016)
An efficient multicomponent protocol has been developed to access two different kinds of peptide–ecdysteroid conjugates. The approach exploits the reactivity of the 6-keto-7-ene group of 20-OH-ecdysone, allowing the unprecedented preparation of 6-amino and 6-isocyanide derivatives. The ecdysteroid derivatives were further employed in the Ugi reaction, together with formaldehyde and various structurally diverse carboxylic acids, isocyanides and amines, to afford a small family of potential multidrug-resistance modulators.
Keywords: steroids; peptide-steroid conjugates; multicomponent reactions; Ugi reaction; multidrug resistance